Professional competence of teaching staff in the context of modern education (Pedagogy of Higher and Secondary Education, 2012)
Stoychik T. Professional competence of teaching staff in the context of modern education.In the article actual problem of improvement of professional competence of teachers vocational and technical educational institutions in accordance with modern requirements.
Keywords: competence; professional competence; self-education; advanced training